2014
DOI: 10.1007/s12663-013-0609-1
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study to Assess the Levels of Interleukin-6 Following Administration of Diclofenac, Ketorolac and Tramadol After Surgical Removal of Lower Third Molars

Abstract: Introduction The surgical removal of impacted third molars involves, trauma to soft and bony tissue and can result in considerable pain, swelling, and trismus. The greater the amount of tissue injury the greater is the amount of inflammation in the perisurgical region. Interleukin-6 (IL-6) is both a pro inflammatory and anti-inflammatory cytokine. It is secreted by T cells and macrophages to stimulate the immune response. IL-6 is also an early marker of tissue damage. In addition to NSAIDs, corticosteroids, op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 13 publications
2
19
3
Order By: Relevance
“…Because cytokines were measured in serum, they might have been released from activated cells rather than representing circulating levels. In contrast with some prior studies, 36,37 ibuprofen treatment did not decrease IL-6 levels in our cohort. This may be due to differences in timing of sample collection, as our samples were collected ~ 3 and 5 hours after surgery, whereas effects of NSAIDs on cytokine levels have been observed at later time points (e.g., 12-24 hours after surgery).…”
Section: Discussioncontrasting
confidence: 99%
“…Because cytokines were measured in serum, they might have been released from activated cells rather than representing circulating levels. In contrast with some prior studies, 36,37 ibuprofen treatment did not decrease IL-6 levels in our cohort. This may be due to differences in timing of sample collection, as our samples were collected ~ 3 and 5 hours after surgery, whereas effects of NSAIDs on cytokine levels have been observed at later time points (e.g., 12-24 hours after surgery).…”
Section: Discussioncontrasting
confidence: 99%
“…However, it is also possible that these pathways are regulated in parallel, and additional studies are necessary to clarify whether there is a causal relationship between activation of the COX pathway and induction of TNF-α and IL-8 in vivo. In contrast to some prior studies [51,52], ibuprofen treatment did not decrease IL-6 levels in our cohort. This may be due to differences in timing of sample collection as our samples were collected approximately 3 and 5 hours after surgery, while effects of NSAIDs on cytokine levels have been observed at later time points (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…The results obtained at postoperative hour 24 showed a significant increase in IL-6 levels compared to the pre-operative results. These findings are identical to the results of studies of some authors, according to whom IL-6 levels are highest at postoperative hour 24, and then decrease [14,19,20]. The analysis of the data obtained by us showed that the rise in IL-6 levels after surgical removal of impacted third molars was not higher than 14 pg/ml.…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that preoperative IL-6 levels were below the LOQ. This is in disagreement with studies by other authors [13,14]. In our opinion, the reason for this is the inclusion and exclusion criteria of the study, which were defined so to eliminate the phenomenon of central sensitization.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation